Molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material, preparation method and application
By using molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material in sodium ion battery material, the WS2 and MoS2 material layers are grown by heat treatment and two-step thermal reaction method, the problem of insufficient capacity of sodium ion battery material under large current density is solved, and high energy density and excellent cycling stability are achieved.
Patent Information
- Application Number
- CN202210864675.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-07-21
AI Technical Summary
Existing sodium ion battery materials cannot provide high capacity at high current density, and the low electronic conductivity and volume expansion problems of transition metal sulfides lead to rapid attenuation of capacity.
Molybdenum disulfide@tungsten disulfide@carbon cloth electrode material is adopted, and the 1T phase WS2 and MoS2 material layers are uniformly grown through heat treatment on the conductive carbon cloth and a two-step thermal reaction method, expanding the layer spacing, improving energy density and cycling stability.
It achieves high energy density, excellent cycling stability and rate performance, is suitable for sodium ion battery negative electrode materials applications, and can provide stable and high capacity under high current density.
Smart Images

Figure CN115207285B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sodium ion battery materials, and specifically relates to a molybdenum disulfide@tungsten disulfide@carbon cloth electrode material, a preparation method and an application thereof. Background Art
[0002] With the increase of energy consumption and greenhouse gas emissions worldwide, people are paying more and more attention to the research and development of new energy technologies in order to ensure the clean supply of energy in the future. In recent years, rechargeable batteries have been widely studied and play an important role in modern life. The practical application of high energy density and long cycle lithium-ion batteries has made great achievements and has been widely used in daily life, such as electric vehicles, mobile phones, etc. Unfortunately, the high price and low availability of metallic lithium have seriously hindered its further development. Sodium-ion batteries have attracted widespread attention due to their low cost, wide distribution, simple refining, high resource utilization rate and similar physical and chemical properties to lithium-ion batteries. However, it cannot be ignored that the radius of sodium ions is larger than that of lithium ions, which makes sodium ions more inclined to embed into the anion interstitial sites of oxygen ion octahedral or triangular prism configurations with larger space during the process of embedding into the crystal structure of the material. In addition, the relative atomic mass of sodium ions is greater than that of lithium ions, and the electrode potential of sodium ions is about 300mV higher than that of lithium ions. These factors work together to cause the mass energy density of sodium-ion batteries to be lower than that of lithium-ion batteries.
[0003] At present, energy technology has achieved a transcendent development, which also puts forward the requirement for sodium-ion batteries to provide high capacity at high current density. Therefore, the key technology to promote the further promotion and application of sodium-ion batteries lies in how to prepare sodium-ion battery materials with high stability, high energy density and suitable for high-rate operation.
[0004] Transition metal sulfides have the characteristics of high theoretical capacity and controllable micromorphology, and are considered to be a very promising type of negative electrode material for sodium ion batteries. However, the low electronic conductivity of transition metal sulfides is not conducive to electrode reactions, and the conventional interlayer spacing can no longer meet the needs of more efficient insertion and extraction of sodium ions. In addition, transition metal sulfides experience severe volume expansion during the charge and discharge process, resulting in pulverization and loose contact of active materials, which ultimately leads to rapid capacity decay during high-rate charge and discharge, and cannot meet the high-rate charge and discharge requirements of sodium ion electrode materials. Summary of the invention
[0005] In order to solve the above problems, one of the objects of the present invention is to provide a method for preparing molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material, which has simple operation and mild reaction conditions, and the prepared electrode material not only has a large interlayer spacing, but also has high energy density, excellent cycle stability and rate performance, and is suitable for application as a negative electrode material for sodium ion batteries.
[0006] The second object of the present invention is to provide a molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material, which is a nanocomposite material obtained by sequentially and uniformly growing 1T phase tungsten disulfide and 1T phase molybdenum disulfide on the surface of carbon cloth. It not only has a large interlayer spacing, which is suitable for sodium ion embedding and extraction, but also has high energy density, excellent cycle stability and rate performance, and is suitable for application as a negative electrode material for sodium ion batteries.
[0007] The third object of the present invention is to provide an application of molybdenum disulfide@tungsten disulfide@carbon cloth electrode material.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The preparation method of molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material comprises the following steps:
[0010] 1) placing the conductive carbon in concentrated nitric acid for heat treatment, washing and drying after cooling to obtain a pretreated carbon cloth;
[0011] Separately, tungsten salt and thioacetamide are stirred and dissolved in an organic solvent to obtain a precursor A;
[0012] Separately, molybdenum salt and L-cysteine were stirred and dissolved in deionized water to obtain precursor B;
[0013] 2) Solvent thermally reacting the pretreated carbon cloth and the precursor A at 190-210° C. for 18-22 hours, and then washing and drying to obtain a tungsten disulfide@carbon cloth composite material;
[0014] 3) The tungsten disulfide@carbon cloth composite material and the precursor B are hydrothermally reacted at 170-190° C. for 46-50 hours, and then washed and dried to obtain the molybdenum disulfide@tungsten disulfide@carbon cloth electrode material.
[0015] The preparation method of the present invention is simple to operate, mild in conditions and high in yield. The present invention synthesizes a novel molybdenum disulfide@tungsten disulfide@carbon cloth composite nanomaterial by a simple two-step thermal reaction method.
[0016] Among them, the conductive carbon cloth substrate can promote the formation of a conductive network during the charge and discharge process, while improving the conductivity, increasing the reactive sites and accelerating the electrochemical reaction. In addition, the carbon cloth after heat treatment with concentrated nitric acid can effectively inhibit the material aggregation phenomenon, reduce the volume expansion rate of the material, and thus improve the material's cycle stability and rate performance.
[0017] Furthermore, the present invention successfully loaded and uniformly grew 1T phase WS on the conductive carbon cloth through a two-step thermal reaction process and controlled the type of precursor raw materials. 2 Material layer, 1T phase MoS 2Material layer. Among them, WS 2 、MoS 2 With uniform nanosheet morphology, WS 2 The addition of can reduce the MoS 2 The materials agglomerate and synergistically improve the material specific capacity. On the other hand, it can also effectively expand the MoS 2 The material interlayer spacing provides convenient conditions for the interlayer insertion and extraction of sodium ions, which is beneficial to the insertion and extraction of sodium ions without causing large volume expansion, thereby improving the rate performance and cycle stability of the electrode material, and at the same time improving the discharge capacity of the sodium ion battery.
[0018] In the present invention, concentrated nitric acid is used to treat the conductive carbon cloth, which can leave abundant small holes on the surface of the carbon cloth, thereby improving the roughness of the material surface. Moreover, after the concentrated nitric acid treatment, more hydrophilic active groups can be formed on the carbon cloth, thereby greatly promoting the WS reaction during the heat treatment process. 2 、MoS 2 The uniform growth on the surface of the carbon cloth material ensures the material performance. Preferably, in step 1), the heat treatment is 80-100°C for 5-7 hours, more preferably 90°C for 6 hours.
[0019] In the present invention, there is no special restriction on the types of organic solvent, tungsten salt and molybdenum salt, and they can be selected according to existing materials, as long as they meet the requirements for the synthesis and preparation of nanocomposite materials during the thermal reaction. Further, in step 1), the organic solvent is methyl pyrrolidone; the tungsten salt is sodium tungstate; and the molybdenum salt is sodium molybdate.
[0020] The present invention first adopts a solvent thermal method and then a hydrothermal method to prepare a composite material. The above preparation process is a method in which a solvent or water is used as a reaction system in a high-pressure reactor, and a relatively high-temperature and high-pressure reaction environment is created by heating and pressurizing the reaction system so that the substances react to synthesize the material. In the present invention, in order to effectively obtain a precursor that conforms to a solvent thermal reaction or a hydrothermal reaction, to achieve comprehensive control of the morphology and microstructure of the nanomaterial, thereby expanding the material interlayer spacing, and improving the rate and cycle performance of the material, preferably, in step 2), the temperature of the solvent thermal reaction is 200°C and the time is 20h; in step 3), the temperature of the hydrothermal reaction is 180°C and the time is 48h.
[0021] As a further preferred scheme of the thermal reaction process, in step 1), the usage ratio of the tungsten salt, thioacetamide, and organic solvent is (1.1-1.3) g: (1.4-1.6) g: (55-65) mL, and more preferably 1.2 g: 1.5 g: 60 mL. Further preferably, the usage ratio of the molybdenum salt, L-cysteine amine, and deionized water is (1.1-1.3) g: (2.4-2.6) g: (70-80) mL, and more preferably 1.2 g: 2.5 g: 75 mL. The above raw materials are used as precursors to prepare raw materials, which are materials whose morphology meets the preparation requirements after screening different raw materials by thermal reaction in the present invention, and can ensure that the prepared WS 2 、MoS 2 It is a 1T stable phase and is uniformly loaded on the substrate in large quantities.
[0022] Preferably, in steps 2) and 3), the washing is performed by alternating washing with ethanol and deionized water.
[0023] The molybdenum disulfide@tungsten disulfide@carbon cloth electrode material of the present invention is prepared by the above-mentioned preparation method.
[0024] The application of the molybdenum disulfide@tungsten disulfide@carbon cloth electrode material of the present invention is specifically its application in the negative electrode material of sodium ion battery.
[0025] The molybdenum disulfide@tungsten disulfide@carbon cloth electrode material of the present invention has the advantages of good conductivity, large interlayer spacing (about 1 nm), uniform morphology and low cost. It also has unique sodium storage performance, high specific capacity, excellent rate and cycle stability, and is suitable for promotion and application in sodium ion batteries.
[0026] In addition, the molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material prepared by the present invention is a self-supporting flexible substrate material with a high content of active substances and a large loading capacity. The prepared composite electrode material can be directly used as an electrode material without the need for further processing, eliminating the use of conductive agents and adhesives, simplifying the assembly steps of the battery, and can greatly improve the battery assembly efficiency and reduce processing costs.
[0027] The electrochemical experimental results confirm that the design of the molybdenum disulfide @ tungsten disulfide @ carbon cloth composite electrode material of the present invention significantly improves the MoS 2 The utilization rate of the sodium ion battery is improved, the reversible capacity, cycle stability and rate performance of the sodium ion battery are improved, and it is expected to be used in large-scale energy storage systems. At the same time, the design idea of the invention also provides a theoretical reference for the development of new materials with strong practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1This is a low-magnification scanning electron microscope (SEM) image of the molybdenum disulfide @ tungsten disulfide @ carbon cloth material prepared in Example 1 of the present invention;
[0029] Figure 2 This is a high-magnification scanning electron microscope (SEM) image of the molybdenum disulfide @ tungsten disulfide @ carbon cloth material prepared in Example 1 of the present invention;
[0030] Figure 3 This is a transmission electron microscope (TEM) image of the molybdenum disulfide @ tungsten disulfide @ carbon cloth material prepared in Example 1 of the present invention;
[0031] Figure 4 This is a high-resolution transmission electron microscopy (HRTEM) image of the molybdenum disulfide @ tungsten disulfide @ carbon cloth material prepared in Example 1 of the present invention;
[0032] Figure 5 This is an X-ray diffraction (XRD) diagram of the molybdenum disulfide @ tungsten disulfide @ carbon cloth material prepared in Example 1 of the present invention;
[0033] Figure 6 This is a rate performance diagram of the molybdenum disulfide @ tungsten disulfide @ carbon cloth material prepared in Example 1 of the present invention as a negative electrode material for a sodium ion battery at different discharge rates;
[0034] Figure 7 This is a cycle performance curve of the molybdenum disulfide@tungsten disulfide@carbon cloth material prepared in Example 1 of the present invention as a negative electrode material for a sodium ion battery at a 1C rate. DETAILED DESCRIPTION
[0035] The following is a further introduction to the technical solution of the present invention in conjunction with the accompanying drawings and specific implementation methods, but does not constitute a limitation of the present invention. In the following embodiments, the conductive carbon cloth model used is wos1009; the concentrated nitric acid used is a conventional commercial product with a mass fraction of 68%.
[0036] Example 1
[0037] The molybdenum disulfide@tungsten disulfide@carbon cloth electrode material of this embodiment is prepared by a method comprising the following steps:
[0038] 1) placing the conductive carbon cloth in concentrated nitric acid, heating at 90° C. for 6 h, cooling and ultrasonically cleaning with deionized water until neutral, and vacuum drying at 60° C. for 12 h to obtain the pretreated carbon cloth;
[0039] Separately, 1.2 g of sodium tungstate and 1.5 g of thioacetamide were dissolved in 60 mL of methyl pyrrolidone solution and stirred for 1 h to obtain precursor A;
[0040] Separately, 1.2 g of sodium molybdate and 2.5 g of L-cysteine were dissolved in 75 mL of deionized water and stirred for 3 h to obtain precursor B;
[0041] 2) Pour the pretreated carbon cloth and precursor A into the reactor at the same time, react at 200°C for 20 hours, and after the reaction is completed, use ethanol and deionized water to alternately ultrasonically clean for several times, and then vacuum dry at 60°C for 12 hours to obtain a tungsten disulfide@carbon cloth composite material;
[0042] 3) The tungsten disulfide@carbon cloth composite material and precursor B are placed in a reactor together, and subjected to hydrothermal reaction at 180°C for 48 hours. After cooling, the composite material is ultrasonically cleaned alternately with ethanol and deionized water for several times, and then vacuum dried at 60°C for 12 hours to obtain molybdenum disulfide@tungsten disulfide@carbon cloth electrode material.
[0043] Example 2
[0044] The molybdenum disulfide@tungsten disulfide@carbon cloth electrode material of this embodiment is prepared by a method comprising the following steps:
[0045] 1) placing the conductive carbon cloth in concentrated nitric acid, heating it at 100° C. for 5 h, and then ultrasonically cleaning it with deionized water until it becomes neutral after cooling, and vacuum drying it at 60° C. for 12 h to obtain the pretreated carbon cloth;
[0046] Separately, 1.3 g of sodium tungstate and 1.6 g of thioacetamide were dissolved in 65 mL of methyl pyrrolidone solution and stirred for 1 h to obtain precursor A;
[0047] Separately, 1.3 g of sodium molybdate and 2.6 g of L-cysteine were dissolved in 80 mL of deionized water and stirred for 3 h to obtain precursor B;
[0048] 2) Pour the pretreated carbon cloth and precursor A into the reactor at the same time, react at 210°C for 18 hours, and after the reaction is completed, use ethanol and deionized water to alternately ultrasonically clean for several times, and then vacuum dry at 60°C for 12 hours to obtain a tungsten disulfide@carbon cloth composite material;
[0049] 3) The tungsten disulfide@carbon cloth composite material and precursor B are placed in a reactor together, and hydrothermally reacted at 190°C for 46 hours. After cooling, ethanol and deionized water are used for alternating ultrasonic cleaning for several times, and then vacuum dried at 60°C for 12 hours to obtain molybdenum disulfide@tungsten disulfide@carbon cloth electrode material.
[0050] Example 3
[0051] The molybdenum disulfide@tungsten disulfide@carbon cloth electrode material of this embodiment is prepared by a method comprising the following steps:
[0052] 1) placing the conductive carbon cloth in concentrated nitric acid, heating it at 80° C. for 7 h, and then ultrasonically cleaning it with deionized water until it becomes neutral after cooling, and vacuum drying it at 60° C. for 12 h to obtain the pretreated carbon cloth;
[0053] Separately, 1.1 g of sodium tungstate and 1.4 g of thioacetamide were dissolved in 55 mL of methyl pyrrolidone solution and stirred for 1 h to obtain precursor A;
[0054] Separately, 1.1 g of sodium molybdate and 2.4 g of L-cysteine were dissolved in 70 mL of deionized water and stirred for 3 h to obtain precursor B;
[0055] 2) Pour the pretreated carbon cloth and precursor A into the reactor at the same time, react at 190°C for 22 hours, and after the reaction is completed, use ethanol and deionized water to alternately ultrasonically clean for several times, and then vacuum dry at 60°C for 12 hours to obtain a tungsten disulfide@carbon cloth composite material;
[0056] 3) The tungsten disulfide@carbon cloth composite material and precursor B are placed in a reactor together, and hydrothermally reacted at 170°C for 50 hours. After cooling, ultrasonic cleaning is performed alternately with ethanol and deionized water for several times, and then vacuum dried at 60°C for 12 hours to obtain molybdenum disulfide@tungsten disulfide@carbon cloth electrode material.
[0057] Comparative Example 1
[0058] The electrode material of this comparative example adopts a preparation method different from that of Example 1 in that: in step 1), the preparation process of precursor A is omitted, step 2) is completely omitted, and in step 3), the pretreated carbon cloth and precursor B are directly placed in a reactor for reaction, and the remaining steps and parameters are the same as those of Example 1.
[0059] Comparative Example 2
[0060] The preparation method of the electrode material in this comparative example is different from that in Example 1 in that the preparation process of precursor B is omitted in step 1), step 3) is completely omitted, and the remaining steps and parameters are the same as in Example 1.
[0061] Comparative Example 3
[0062] The electrode material of this comparative example adopts a preparation method different from that of Example 1 in that steps 2) and 3) are combined, i.e., the pretreated carbon cloth, precursor A, and precursor B are directly poured into the reactor at the same time, and hydrothermally reacted at 180°C for 48 hours. After cooling, the mixture is ultrasonically cleaned alternately with ethanol and deionized water for several times, and then vacuum dried for 12 hours to obtain a ternary composite electrode material.
[0063] Experimental Example 1 Structural Characterization of Electrode Materials
[0064] The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the electrode material of Example 1 were obtained by electron microscope and projection electron microscope, and then the electrode material of Example 1 was subjected to X-ray diffraction to obtain an X-ray diffraction pattern (XRD). The results are as follows: Figures 1 to 5 shown.
[0065] Depend on Figure 1 , 2 The SEM results show that there are many small holes on the surface of the carbon cloth after concentrated nitric acid treatment, which is conducive to the WS 2 、MoS 2 The uniform growth on the surface of the material, therefore, using carbon fiber as a matrix for loading nanomaterials can not only construct a three-dimensional channel, shorten the path of ion diffusion, but also improve the conductivity of the material. In addition, it can be seen from the figure that the surface of the carbon cloth is almost not exposed, WS 2 、MoS 2 The nanosheet material grows well on the surface of the carbon fiber, and the surface of the carbon cloth is completely covered by the nanosheet material, which also indirectly verifies the authenticity of the high-load electrode obtained by the present invention. In addition, the nanomaterial-coated layer is very thin, evenly distributed, and has a large spacing. This nanosheet morphology is very beneficial for the full penetration of the electrolyte and the smooth extraction and embedding of sodium ions during the charge and discharge process.
[0066] Further by Figure 3 , 4 From the TEM results, it can be seen that WS 2 、MoS 2 It has a uniform nanosheet morphology and is all 1T phase. In addition, the MoS 2 The interlayer spacing is about 1.012nm, which is much higher than that of ordinary MoS 2 The interlayer spacing is 0.629 nm, which is also much higher than the MoS in Comparative Example 1. 2 The interlayer spacing of the material is 0.75nm, while WS 2 The interlayer spacing is about 0.983 nm, which is also significantly higher than the interlayer spacing of the single material in Comparative Example 2. This shows that the material prepared by the present invention is more suitable for sodium storage. The huge interlayer spacing facilitates the embedding and extraction of sodium ions, reduces the resistance to sodium ion diffusion, and is beneficial to improving the electrochemical properties of the prepared material.
[0067] Depend on Figure 5 It can be seen from the XRD results that the XRD diffraction peak of the material is similar to that of MoS 2 and WS 2 The standard card is basically consistent, indicating the successful preparation of MoS2@Tungsten Disulfide@Carbon Cloth electrode material. (002) peak is MoS 2 and WS 2 It can be clearly seen from the figure that the (002) peak of the molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material has shifted. According to the Bragg equation, the interlayer spacing corresponding to the (002) peak is about 0.99nm. This shows that the interlayer spacing of the electrode material has increased significantly through the reaction. It can be seen that the introduction of carbon substrate and tungsten sulfide can significantly reduce the MoS 2 Material agglomeration and significant expansion of MoS 2The interlayer spacing is more conducive to the insertion and extraction of sodium ions.
[0068] Experimental Example 2 Electrochemical Performance Test of Sodium Ion Battery
[0069] Battery assembly: Sodium sheet was used as counter electrode, circular electrode sheet cut from electrode material prepared in Example 1 and Comparative Examples 1 to 3 of the present invention was directly used as working electrode, microporous polypropylene membrane was used as diaphragm, 1 mol / L NaCl 4 / EC (ethylene carbonate) + DMC (dimethyl carbonate) + FEC (fluoroethylene carbonate) as electrolyte (NaCLO in electrolyte) 4 As the solute, the volume ratio of solvent EC+DMC+FEC is 1:1:1), and the CR 2016 button cells are assembled in a glove box filled with high-purity argon and sealed.
[0070] Performance test: The assembled battery was placed for 6 to 12 hours before electrochemical testing. The sodium ion battery cycle test was completed at room temperature on the Blue Electric Battery Test System CTA (CT2001A Wuhan Blue Electric Electronics Co., Ltd.), with a voltage range of 0.01-3.0V. The electrochemical AC impedance test was completed on the electrochemical workstation (CHI660D), with a test frequency range of 0.1-100KHz. The results are shown in Table 1 and Figure 6 , 7 shown.
[0071] Rate performance is an important indicator for evaluating the electrochemical performance of batteries, and it also meets the current requirements for sodium ion batteries to provide high capacity at high current density. Therefore, observing the charge and discharge specific capacity at different current densities can determine the rate performance of the battery. The rate performance of the sodium ion battery using the molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material prepared in Example 1 as the working electrode was tested at different current densities. Figure 6 As shown, the prepared MoS2@Tungsten Disulfide@Carbon Cloth electrode material electrode is heated at 1C, 2C, 5C, 8C, and 10C (corresponding to 0.1, 0.2, 0.5, 0.8, and 1.0 Ag -1 The discharge capacities were 546, 478, 367, 331 and 207 mAh g -1 , proving that the prepared electrode has excellent rate performance. The reason is that the conductive carbon cloth plays the role of dispersion and conductive substrate for the nanosheets, and the abundant conductive points and conductive paths can increase the electrochemical reaction rate. In addition, WS 2 and MoS 2 The larger interlayer spacing improves the ion transfer rate and can effectively inhibit the volume expansion of the nanosheets, thereby synergistically improving the material rate performance.
[0072] The cycle performance of the sodium ion battery using the molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material prepared in Example 1 as the working electrode was tested. The cycle performance is another criterion for evaluating the performance of sodium ion batteries. Relevant information can be obtained by observing its specific capacity, cycle life and coulombic efficiency. Figure 7 MoS2@Tungsten Disulfide@Carbon Cloth Electrode Material at 1C rate (corresponding to 0.1Ag -1 Performance of 100 charge and discharge cycles at high current density.
[0073] Depend on Figure 7 It can be seen that in the first cycle, the initial discharge capacity is 1097.1 mAh g -1 , charging capacity is 734.4mAh g -1 , with a Coulombic efficiency of 66.94%. The insufficient specific capacity in the initial cycle is mainly due to the formation of SEI and moderate irreversible conversion reactions. In the subsequent 100 cycles, the capacity stabilized at 528.9 mAh g -1 , the capacity retention is good. Combining SEM and TEM images, the designed nanomaterial has thin layer thickness, high stacking density, and large interlayer spacing, which is conducive to the full penetration of the electrolyte, improving the electrochemical rate during the charge and discharge process, thereby comprehensively improving the cycle performance.
[0074] The same method as in Experimental Example 1 was further used to test the performance of the electrode materials obtained in Comparative Examples 1 to 3 as negative electrode materials for sodium ion batteries. The results are shown in Table 1.
[0075] Table 1 Comparison of rate performance of different electrode materials
[0076]
[0077] As can be seen from Table 1, the material of Comparative Example 1 is molybdenum disulfide @ carbon cloth electrode material, which has a good capacity retention rate and slow capacity decay rate at high rate discharge, but due to the short interlayer spacing, the resistance to sodium ion insertion and removal is large, and the molybdenum disulfide material is easy to agglomerate, resulting in a large volume expansion when sodium ions are inserted and removed, resulting in the electrode material The specific capacity and rate performance are still poor. The material of Comparative Example 2 is tungsten disulfide @ carbon cloth electrode material, which has excellent specific capacity at low rate discharge, but the specific capacity has an irreversible drop at high rate discharge, so it cannot meet the high rate use requirements of sodium ion batteries. The material of Comparative Example 3 is a tungsten disulfide @ molybdenum disulfide @ carbon cloth ternary composite material prepared by a one-step method. Compared with the embodiment of the present invention, it has relatively poor specific capacity and rate performance, indicating that the one-step method is not conducive to the uniform growth of nanomaterials on the surface of carbon cloth, nor does it utilize the synergistic improvement of material specific capacity and rate performance.
[0078] In summary, the molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material of the present invention has the advantages of good conductivity, large interlayer spacing, uniform morphology and low cost. It also has unique sodium storage performance, excellent specific capacity, rate performance and cycle stability, and is suitable for promotion and application in sodium ion batteries.
Claims
1. A method for preparing a molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material, characterized in that: The following steps are involved: 1) placing the conductive carbon in concentrated nitric acid for heat treatment, washing and drying after cooling to obtain a pretreated carbon cloth; Separately, tungsten salt and thioacetamide are stirred and dissolved in an organic solvent to obtain a precursor A; Separately, molybdenum salt and L-cysteine were stirred and dissolved in deionized water to obtain precursor B; 2) Solvent thermally reacting the pretreated carbon cloth and the precursor A at 190-210° C. for 18-22 hours, and then washing and drying to obtain a tungsten disulfide@carbon cloth composite material; 3) The tungsten disulfide@carbon cloth composite material and the precursor B are hydrothermally reacted at 170-190° C. for 46-50 hours, and then washed and dried to obtain the molybdenum disulfide@tungsten disulfide@carbon cloth electrode material.
2. The method for preparing the molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material according to claim 1, characterized in that: In step 1), the heat treatment is performed at 80-100° C. for 5-7 hours.
3. The method for preparing the molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material according to claim 1, characterized in that: In step 1), the organic solvent is methyl pyrrolidone; the tungsten salt is sodium tungstate; and the molybdenum salt is sodium molybdate.
4. The method for preparing the molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material according to claim 1 or 3, characterized in that: In step 1), the usage ratio of the tungsten salt, thioacetamide and organic solvent is (1.1-1.3) g: (1.4-1.6) g: (55-65) mL.
5. The method for preparing the molybdenum disulfide@tungsten disulfide@carbon cloth electrode material according to claim 1 or 3, characterized in that: In step 1), the molybdenum salt, L-cysteine and deionized water are used in a ratio of (1.1-1.3) g: (2.4-2.6) g: (70-80) mL.
6. The method for preparing the molybdenum disulfide@tungsten disulfide@carbon cloth electrode material according to claim 1 or 3, characterized in that: In step 1), the usage ratio of the tungsten salt, thioacetamide and organic solvent is 1.2 g: 1.5 g: 60 mL; the usage ratio of the molybdenum salt, L-cysteine and deionized water is 1.2 g: 2.5 g: 75 mL.
7. The method for preparing the molybdenum disulfide@tungsten disulfide@carbon cloth electrode material according to claim 1, characterized in that: In steps 2) and 3), the washing is performed by alternately washing with ethanol and deionized water.
8. A molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 7.
9. The use of molybdenum disulfide @ tungsten disulfide @ carbon cloth electrode material as claimed in claim 8, characterized in that: Application in negative electrode materials of sodium ion batteries.
Citation Information
Patent Citations
Preparation method of metal phase vanadium / molybdenum disulfide / carbon cloth sodium ion battery negative electrode material
CN111276676A
WS < 2 >-MoS < 2 >-C / rGO electrode material and preparation method and application thereof
CN114203984A